1999
DOI: 10.1128/jb.181.19.5993-6002.1999
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Surface Sensing and Biofilm-Dependent Regulation of Gene Expression in Escherichia coli

Abstract: To get further information on bacterial surface sensing and biofilm-dependent regulation of gene expression in Escherichia coli K-12, random insertion mutagenesis with Mu dX, a mini-Mu carrying the promoterless lacZ gene, was performed with anompR234 adherent strain, and a simple screen was developed to assess changes in gene expression in biofilm cells versus planktonic cells. This screen revealed that major changes in the pattern of gene expression occur during biofilm development: the transcription of 38% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
188
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(195 citation statements)
references
References 50 publications
3
188
0
4
Order By: Relevance
“…It is well known that £agella are directly implicated in the initial adhesion of L. monocytogenes [11] at the beginning of bio¢lm formation. As the synthesis of this protein is inhibited during the bio¢lm development of many motile bacteria [6], this property could be one of the most important to phenotypically characterize bio¢lms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that £agella are directly implicated in the initial adhesion of L. monocytogenes [11] at the beginning of bio¢lm formation. As the synthesis of this protein is inhibited during the bio¢lm development of many motile bacteria [6], this property could be one of the most important to phenotypically characterize bio¢lms.…”
Section: Discussionmentioning
confidence: 99%
“…This property is certainly the result of additive e¡ects of several speci¢c regulatory mechanisms inside the bio¢lms leading to long-term survival. Prigent-Combaret et al [6] reported that the expression of speci¢c genes was modi¢ed in Escherichia coli growing attached to a surface. For most bacteria including L. monocytogenes, limited information is available about the speci¢c properties that are expressed in bio¢lms.…”
Section: Introductionmentioning
confidence: 99%
“…O'Toole et al ., 2000), and the involvement of cellular motility, adhesins, matrix-forming exopolymers, and cell-to-cell signalling has been demonstrated (e.g. Mack et al ., 1994;Heilmann et al ., 1996;Davies et al ., 1998;O'Toole and Kolter, 1998;Pratt and Kolter, 1998;Prigent-Combaret et al ., 1999;Yildiz and Schoolnik, 1999;Danese et al ., 2000;Espinosa-Urgel et al ., 2000;Whitchurch et al ., 2002;Hinsa et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have reported genes required for bio¢lm formation and development by various Gram negative rods [5^7] and Gram positive cocci [8]. Speci¢c expression of selected genes of Escherichia coli growing as a bio¢lm was determined by Prigent-Combaret et al [6], and Perrot et al [9] reported that the proteome of gel-entrapped E. coli cells di¡ered from that of corresponding free £oating cells. Little is known about the physiology of bio¢lmbound Gram positive rods and, to our knowledge, no work regarding the genetic regulation of this mode of growth has been reported.…”
Section: Introductionmentioning
confidence: 99%